THE RELATIONSHIP BETWEEN SELF-MONITORING WITH ACADEMIC PROCRASTINATION OF STUDENTS WHO ARE WORKING ON THESIS AT FACULTY OF PSYCHOLOGY IN UNIVERSITY OF DIPONEGORO - Nur Amelia Sari; Endah Kumala Dewi; Ika Febrian Kristiana (Faculty of Psychology, Diponegoro University, 2012)
This research was conducted to determine the relationship between self-monitoring with academic procrastination in students who are working on thesis at the Faculty of Psychology, University of Diponegoro. The population is 123 students with a sample of 60 students. Determination of the samples was done by using simple random sampling. Data collection tool in the study of academic procrastination is a scale consisting of 38 aitem (α = .940) and self-monitoring scale consists of 25 aitem (α = 0.924), which has been tested.The data obtained showed a correlation coefficient of -0.454 with p = 0.000 (p <0.05), meaning that there is a significant negative relationship between self-monitoring with academic procrastination in students who are working on thesis at the Faculty of Psychology, University of Diponegoro. The higher self-monitoring, the lower the academic procrastination in students who are working on the thesis. Conversely, the lower the self-monitoring, the higher the academic procrastination in students who are working on the thesis. Self-monitoring variables contribute effectively to academic procrastination by 20.6%, while 79.4% came from other factors that are not revealed in this study.